Anthropic soils in the upper Ecuadorian Amazon?: Geo-archaeological studies in the dumpsite of La Lomita, Upano valley, Morona Santiago, Ecuador - Velasco Albán, Janny Mauricio (Centro de Publicaciones Pontificia Universidad Católica del Ecuador, 2021)
The archaeological research in recent decades has developed important contributions tounderstanding the emergence of complex societies in Amazon rainforest ecosystems, specificallyin the upper Upano basin of the High-Amazonia in Ecuador, an extensive area in the peri-Andeanfoothills modified by artificial earth mounds organized in complex patterns of settlements. Theseconstructive processes started around 380 B.C., giving place to almost a millennium of occupationcharacterized by the presence of Upano ceramic tradition. The concentration of earth moundsbrings up questions about the impacts of human occupation in Amazonian landscapes and the needto include analytic methods to obtain new information. This work brings to the debate aboutanthropic soils a case study in the Ecuadorian Amazon, applying chemical analysis to soil samplesfrom Basural La Lomita, belonging to the Huapula Monticular Complex in the upper Upano basin,for characterization and comparative analysis. The results obtained point to the impacts of humanoccupation on the soils of the Upano earth mound settlements, and the potential to understand theprolonged modification of the Amazonian landscapes in pre-Columbian times.